Promoting Education for Sustainable Development: A Collaborative Project Between a Higher Education Institution and the Surrounding School Community - Mateus, D. M. R. (2022)
This chapter describes good practices developed by a higher education institution from Portugal in the context of the United Nations Sustainable Development Goals (SDG). In addition to discussing the role of higher education in society, it also focuses on an intervention project on the local school community aimed at raising awareness and disseminating good attitudes related to Sustainable Development (SD). The intervention project results from a partnership between a higher education institution, a teachers training centre and schools. In this context, several hands-on experiments were developed by higher education teachers, researchers and students, and implemented in a teachers’ professional development programme. Based on questionnaires (N = 63) and participant observation, an empirical study was conducted. Besides increasing their knowledge about SDG, teachers recognized the role of schools in raising awareness to promote SD practices, and valued the role of higher education in supporting them in these initiatives. It is concluded on the importance of developing collaborative partnerships with schools and other stakeholders to raise awareness, disseminate and increase SD practices in the community. The experience developed in the field may interest researchers, policymakers, and anyone interested in promoting Sustainable Development initiatives.